Association of Interleukin 6 and Interleukin 8 genes polymorphisms with house dust mite-induced nasal-bronchial allergy in a sample of Indian patients - Debarati Dey; Priti Mondal; Saibal Moitra; Goutam Kumar Saha; Sanjoy Podder (Egyptian Journal of Medical Human Genetics, 2022)
Abstract Background Genetic background of nasal-bronchial allergy (NBA) is well documented. House Dust Mites (HDMs) are reported to elicit NBA symptoms. Susceptibility to HDM sensitization varies considerably from person to person. Interleukin 6 (IL 6) and Interleukin 8 (IL 8) are studied previously for genetic association with several diseases. To the best of our knowledge, the genetic association of HDM-induced NBA has not been largely reported from India. The aim of our present study was to evaluate any possible association of IL 6 and IL 8 gene polymorphisms with HDM-induced NBA in an Indian population. Methods IL 6 (− 572G/C, − 597G/A) and IL 8 polymorphisms (− 251A/T, + 781C/T) were analyzed in a HDM-sensitized group (N = 372) and a control group (N = 110). Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR–RFLP) based genotyping was done. Chi-square test and Fisher’s exact tests were applied for statistical analysis. Results IL 6 − 597G/A and IL 8 + 781C/T were not associated with HDM-sensitization, while IL 6 − 72G/C and IL 8 − 51A/T showed significant associations in terms of both genotype and allele frequencies. For both the SNPs, minor allele frequencies were significantly higher in the patients compared to the control. Moreover, IL 6 -572G/C and IL 8 -251A/T were found to be strongly linked with HDM sensitization and severity. Conclusion This is probably the pioneer study to describe the association of IL 6 and IL 8 polymorphisms with HDM sensitization in any Indian population. The results suggested that IL 6 -572G/C and IL 8 -251A/T may exert a risk of HDM sensitization leading to NBA.